The death of glory the Western Front 1915 - Neillands, Robin 1935-2006 (John Murray, 2006)
To this day, World War I remains a source of misunderstanding; the bitter reality of the conflict is often clouded by various myths and falsehoods. Many of these misconceptions suggest that the ineptitude of the generals on both sides of the trenches led to the gruesome stalemates and battles. This well-researched and highly readable account reveals the truth behind this fallacy and other events by setting them in a wider context. In 1915 the burden of fighting was shifting from the British Army to the Territorial Forces who were enthusiastic amateurs at best. The battles were either disasters or inconclusive, but the real reason for the failures was that the war-which originally began in the name of liberation for Belgium-had lost its moral argument and was now just another bloody, senseless slaughter. Millions died on the Western Front in 1915 on muddy battlefields, and as this study reveals, there was no glory attached to their deaths.